La voluntad general y sus condiciones de racionalidad - Rempel, Martín (2016)
"This work constitutes an attempt of constructing a bridge that connects Kenneth Arrow's rationality criteria in the framework of the rational choice theory, and the properties of Jean-Jacques Rousseau's Doctrine of the General Will, as exposed in his Social Contract. The object of this work is to elaborate a critical analysis of that bridge."